Persepsi Mahasiswa terhadap Penggunaan Eldiru sebagai Media Pembelajaran Asinkron - Eka Dyah Puspita Sari; Indah Puspitasari (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2022)
Pandemic condition due to Covid-19 disease pushes a new trend in teaching learning activity. It forces all levels of education implementing online learning platforms. Online learning platform gives freedom for students to learn autonomously. There are many online learning platforms available in this pandemic condition. One of the online learning platforms is eLDirU (e-Learning Jenderal Soedirman University). eLDirU is an online learning platform developed by Jenderal Soedirman University. It functions as a digital literacy learning innovation for native digital generation. In eLDirU, students and lecturers can interact in many activities provided in it. Students utilize eLDirU as synchronous and asynchronous learning media. This study observes students’ perception on using eLDirU as asynchronous learning media. 66 students worked as the subject of this study. 66 feedbacks were collected from students’ answers on questionnaires. The result of the questionnaire showed that eLDirU as asynchronous leaning media was proven to be helpful for the students in learning process. Students had a chance to explore themselves more in eLDirU. It also made them more active during learning process because lecturers facilitated the learning process by uploading related materials, videos, and other learning sources in it. Students also found no difficulties in accessing eLDirU, although they stayed in distant area. It might make them enjoy learning on eLDirU. The second result pointed out the use of eLDirU as asynchronous learning media. Students preferred using eLDirU when it came to asynchronous learning. In happened because they could explore their learning sources more with the help of eLDirU. But, for synchronous learning, the use of other learning content management system, such as Zoom meeting and Google Meet, would be students’ top preference. It might ease students’ understanding on the topic better.